2018
DOI: 10.18632/oncotarget.26125
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane inhibits growth and blocks Wnt/β-catenin signaling of colorectal cancer cells

Abstract: The naturally occurring isothiocyanate sulforaphane (SFN) from cruciferous vegetables is associated with growth inhibition of various cancer types, including colorectal cancer. Colorectal cancer is most frequently driven by hyperactive Wnt/β-catenin signaling. Here, we show that SFN treatment reduced growth of three unrelated colorectal cancer cell lines (SW480, DLD1 and HCT116) via induction of cell death and inhibition of proliferation. Importantly, SFN inhibits Wnt/β-catenin signaling in colorectal cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Other chalcones including derricin and derricidin have also been reported to possess such effect when treated to HCT116 colon cancer cell line [ 20 ]. An isothiocyanate compound, sulforaphane, was reported to inhibit canonical Wnt transcriptional activity in two separate studies, as demonstrated by TCF/LEF reporter assays in breast CSCs and colorectal cancer cell lines SW480, DLD1 and HCT116 [ 21 , 22 ]. In this study, while isothiocyanate members consistently exhibited this effect, chalcones did not.…”
Section: Discussionmentioning
confidence: 99%
“…Other chalcones including derricin and derricidin have also been reported to possess such effect when treated to HCT116 colon cancer cell line [ 20 ]. An isothiocyanate compound, sulforaphane, was reported to inhibit canonical Wnt transcriptional activity in two separate studies, as demonstrated by TCF/LEF reporter assays in breast CSCs and colorectal cancer cell lines SW480, DLD1 and HCT116 [ 21 , 22 ]. In this study, while isothiocyanate members consistently exhibited this effect, chalcones did not.…”
Section: Discussionmentioning
confidence: 99%
“…Bernkopf et al . also pointed out that active WNT/β-catenin signaling pathway is the main driving force of colorectal cancer, while SFN can inhibit the growth of colorectal cancer, although no studies have shown a correlation between the two [ 12 ]. Toyama et al .…”
Section: Discussionmentioning
confidence: 99%
“…SFN decreases the activation of p63-iRHOM2 pathway in palmoplantar keratosis and squamous esophageal cancer syndrome (TOC) keratinocytes, leads to the decrease in oxidative stress, inflammation, proliferation and stress response K16, and increases apoptosis [ 11 ]. In addition, there is growing evidence that SFN can inhibit the growth of various types of cancer from different organs, which has aroused interest in the use of SFN in anti-cancer therapy [ 12 ]. The combination of SFN and quercetin has anti-migration effect on melanoma [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated via many molecular mechanisms that SFN induces apoptosis and inhibits proliferation and migration in human colon cancer. [29][30][31][32] SFN can also activate the Nrf2 signaling pathway and protect against H2O2-mediated oxidative damage in normal colonic cells. 33 SAL exhibits antitumor, antibacterial, antifungal, antiparasitic, antiviral and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%